From Typee's Tommo to Moby-Dick's Ishmael: gift exchange in the capitalist world system. Issue 2 (2nd April 2016) - Doan, Caleb
ABSTRACT: Tracking Herman Melville's burgeoning interest in the gift economy, this essay focuses on different modes of exchange in Typee, Mardi, Moby-Dick, and The Confidence-Man . In his early travel novel as well as in his later masterworks, Melville registers the global system of capitalism as it begins to emerge in the Pacific and assert its dominance in the USA. A new reading of the gift principle in Typee, and its infamously problematic ending, recognizes the possibility of a utopian society based on reciprocity. Melville's later works are then analyzed in a similar, but now more explicit, global framework in order to chart a further development in the author's understanding of the capitalist world-system.